A new species of Polianthes subgenus Bravoa (Asparagaceae, Agavoideae) from Jalisco, Mexico - Castro Castro, Arturo; González Gallegos, Jesús Guadalupe; Rodríguez Contreras, Aarón (Phytotaxa, 2015)
During recent botanical explorations in western Mexico, otherwise known as the Nueva Galicia region, a new species of Polianthes subgenus Bravoa was discovered. The new taxon is described and illustrated. It resembles P. bicolor and P. geminiflora var. clivicola, but differs from both by its oblong-obovate and generally prostrate leaves, (3–)4–6(–9) floral nodes, pedicels recurved and 1.1–1.7 cm long in anthesis, perigone tubular, not curved, depressed, and bicolor with imbricate and erect lobes in anthesis, and filaments 1.4–1.6 mm long, inserted in the perigone 1–1.5 mm above ovary tip. Notes on phenology, geographic distribution and habitat of the new species and an identification key to the species of Polianthes subgenus Bravoa growing in western Mexico are also provided.